The court of owls - Cox, Greg (A Batman novel, 2019)
Now Gotham City is plagued with a series of brutal murders. Batman and his allies - including Nightwing and Batgirl - realize the Talons have returned. Should the Owls obtain what they seek, it could grant them power that no one could counter.